Firms pursuit of innovations through internationalization: a treatment effect estimation - Odei, Samuel Amponsah; Stejskal, Jan (Technological and Economic Development of Economy, 2020)
Firms participations in international markets is known to stimulate innovations as well as expose them to both international and domestic partners that can influence their innovation prospects and activities. Countries with weaker innovation potentials acquire advanced knowledge, technologies and innovations when they interact and collaborate with partners in the international ecosystem. The focus of this paper is to explore the linkage between firm’s decisions to internationalize and its additionality effects on firm-level innovations. Our results show a positive and significant correlations between these firms’ participation in international markets and their product, process, research and development and acquisition of external knowledge. We also find that, the foreign enterprise group, foreign clients and customers from the private sector as well as foreign consultants were vital for firms’ innovation. In contrast we find that there is no relationship between foreign ownership and firms’ innovations as can be seen from the insignificant coefficients results. The ATE results show that the extent of internationalizations increased the probabilities of stimulating product, process innovations and R&D on average by 21, 14 and 9 percentage points in comparison with firms that didn’t internationalize. Implications and suggestions for future research are discussed. First published online 8 May 2020